2022
DOI: 10.3390/ijerph19031460
|View full text |Cite
|
Sign up to set email alerts
|

Second Edition of Special Issue “Strategies and Evidence in Health Communication: Evidence and Perspectives”

Abstract: The second edition of this Special Issue “Strategies and Evidence in Health Communication”, published in the International Journal of Environmental Research and Public Health aims primarily to increase international literature evidence and observations in the field regarding: (i) health communication strategies and crisis communication, (ii) health education and health advocacy, and (iii) the fight against the phenomenon of Vaccine Hesitancy (VH) through training and communication activities targeting the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, patients and citizens behave differently according to their cultural backgrounds and beliefs (Zhao 2021). For this reason, hospitals need to collaborate with media companies to adapt health communication messages to citizens' needs (Castiglia and Dettori 2022). Nevertheless, our analysis of French hospitals' online newsrooms revealed that most of them had not implemented true collaborations with media companies to achieve these goals.…”
Section: Discussionmentioning
confidence: 91%
“…However, patients and citizens behave differently according to their cultural backgrounds and beliefs (Zhao 2021). For this reason, hospitals need to collaborate with media companies to adapt health communication messages to citizens' needs (Castiglia and Dettori 2022). Nevertheless, our analysis of French hospitals' online newsrooms revealed that most of them had not implemented true collaborations with media companies to achieve these goals.…”
Section: Discussionmentioning
confidence: 91%
“…This implies that current and future vaccination campaigns should focus on the centrality of the individual and include actions aimed at improving Health Literacy and increasing individuals’ engagement with the health system. Actions must be mainly structured around proper communication of the medical, scientific and social value of vaccination, while also building relationships based on trust, awareness and responsible action [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, bearing in mind the great potential offered by the Internet in health information research processes, health institutions have also chosen to make use of the digital communication channels. Such channels are fundamental to ensure the dissemination of medical–scientific knowledge among user-patients, with the aim of: (i) increasing the spread of high-quality health information; (ii) involving citizens/patients, making them as responsible as possible for their own health; (iii) increasing awareness about infectious diseases and the health treatments available to prevent them [ 21 , 22 , 23 ]. A good example of this is the Italian ‘Vaccinarsì’ network [ 24 ], which is a harbinger of evidence-based messages relayed in consistent terms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the exponential increase in information available online (including health-related content) and the ease of contributing personal opinions and considerations, which are sometimes misleading and lacking scientific evidence, has led to a delegitimisation of the authoritativeness of health information divulged by health professionals [ 7 , 9 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%